Irisin Improves Myocardial Performance and Attenuates Insulin Resistance in Spontaneous Mutation (Leprdb) Mice - Wang, Jianguo; Zhao, Yu Tina; Zhang, Ling; Dubielecka, Patrycja M.; Zhuang, Shougang; Qin, Gangjian; Chin, Yu Eugene; Zhang, Shouyan; Zhao, Ting C. (Frontiers in Pharmacology, 2020)
Background: Irisin, a newly identified hormone, is critical to modulating body metabolism, thermogenesis and reducing oxidative stresses. Our recent works demonstrated that irisin protected the heart against myocardial ischemic injury and preserved the function of mitochondria. However, whether irisin preserves myocardial performance and attenuates insulin resistance in type II diabetes remains unknown. Objective: Effects of irisin on type II-induced cardiac function and insulin resistance in db/db mice were studied. Methods: Homozygous db/db mice for spontaneous mutation (Leprdb) and heterozygous mice for control were used to assess for cardiac performance and impairment of insulin resistance. Homozygous and heterozygous controls received a treatment with either irisin (100mg/kg, intraperitoneal injection, every other day) or vehicle control (PBS) for 4 weeks at sixteen weeks of age. Insulin tolerance test and glucose tolerance test were employed to determine insulin resistance in mice. Cardiac function was assessed by echocardiography. Metabolic features including hyperglycemia and body growth were also examined. Immunohistochemical analysis was employed to determine myocardial hypertrophy and interstitial fibrosis. Immunoblots were employed to determine the signaling pathway associated with irisin treatment. Results: Homozygous db/db mice developed an impairment in insulin sensitivity and hyperglycemia, which were attenuated by administration of irisin. Furthermore, as compared to heterozygous control, db/db mice manifested a progressive depression in cardiac performance in associated myocardial remodeling with an aging progression. Notably, the depression of cardiac function and remodeling were markedly attenuated by the administration of irisin. Western blot shows that irisin treatment prevented the decrease in p38 phosphorylation and increase in HDAC4 in homozygous db/db myocardium. Conclusion: Irisin preserves myocardial performance and insulin resistance in db/db mice, which is related to p38 phosphorylation and HDAC reduction.